Effect of fluctuating hot temperatures on performance and immunity in finishing pigs. - Jensen, M.A.; Blecha, Frank; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Housing pigs in a thermal stress environment reduced gain, intake and feed efficiency. Cell mediated immunity responses were lower under the constant heat stress as well as when the temperature was lowered to a thermal neutral temperature for only 4 hours daily. Daily cooling to thermal neutral for 4, 8, or 16 hours improved growth performance. Antibody responses were not altered by temperature fluctuations.
Keywords: Swine; Fluctuating hot temperatures; Peformance; Immunity